Path-Guided Hierarchical Surface Relief Gratings on Azo-Films Induced by Polarized Light Illumination through Surface-Wrinkling Phase Mask - Zhao, Xiaoxin (Langmuir : the ACS journal of surfaces and colloids, 2020)
Surface relief gratings (SRGs) with hierarchical microstructures are highly needed owing to their diverse applications in various fields. Here, we introduce surface-wrinkling templates as novel nonlithographic phase masks to direct the generation of hierarchical well-prescribed SRGs on nonconformally contacted azo-films by a simple single-beam illumination. The light-induced SRGs have controlled microstructures including single/double/triple wavelengths and single/double orientations as well as their organizations. These microstructures can be well tailored by the wavelength of the surface-wrinkling phase masks and the polarization direction of incident light relative to the wrinkling patterns in the phase masks. Interestingly, we find that the larger wavelength is induced prior to the smaller ones, offering another new strategy to tailor the microstructures of SRGs through simple manipulation of the illumination duration. In particular, path-guided SRGs with unprecedented well-organized hierarchical microstructures have been available in the case of controlled moving of the light illumination through the surface-wrinkling phase mask. As demonstrated, the obtained hierarchical SRGs with the capability of multiple optical inscription/erasure have great application potentials in fields such as confidential information (or pattern) records and encryption/decryption